2020
DOI: 10.3892/or.2020.7456
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑936 inhibits the malignant phenotype of retinoblastoma by directly targeting HDAC9 and deactivating the PI3K/AKT pathway

Abstract: MicroRNA-936 (miR-936) has been reported to play important roles in the progression of non-small cell lung cancer and glioma. However, the expression and functions of miR-936 in retinoblastoma (RB) remain elusive and need to be further elucidated. Herein, the aims were to measure miR-936 expression in RB, identify the functional importance of miR-936 in the oncogenicity of RB, and investigate the underlying molecular mechanisms. Reverse-transcription quantitative PCR was carried out to determine miR-936 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Several recent studies have found that microRNAs (miRs) are involved in post-transcriptional downregulation of HDAC9. Specifically, HDAC9 has been found to be downregulated by miR-188 in bone marrow stromal cells [27], by miR-361-5p in cells associated with cardiac hypertrophy [28], by miR-936 or miR-101-3p in retinoblastoma cells [29,30], by miR-383-5p in gastric carcinoma cells [31], by miR-211-5p in bladder cancer cells [32], by miR-30d-5p in esophageal squamous cell carcinoma cells [33], by miR-509 3p in nonsmall cell lung cancer cells [34] and by miR-377 in oral squamous cell carcinoma cells [35].…”
Section: Specific Hdac9 Expression Patternsmentioning
confidence: 99%
“…Several recent studies have found that microRNAs (miRs) are involved in post-transcriptional downregulation of HDAC9. Specifically, HDAC9 has been found to be downregulated by miR-188 in bone marrow stromal cells [27], by miR-361-5p in cells associated with cardiac hypertrophy [28], by miR-936 or miR-101-3p in retinoblastoma cells [29,30], by miR-383-5p in gastric carcinoma cells [31], by miR-211-5p in bladder cancer cells [32], by miR-30d-5p in esophageal squamous cell carcinoma cells [33], by miR-509 3p in nonsmall cell lung cancer cells [34] and by miR-377 in oral squamous cell carcinoma cells [35].…”
Section: Specific Hdac9 Expression Patternsmentioning
confidence: 99%
“…HDAC genes showed differential regulation in that only the HDAC9 gene was up-regulated, and class I HDACs were down-regulated during the EMT process. A number of studies have shown an involvement of HDAC9 in the ability of migration and invasion [ 20 , 21 , 22 , 23 ]. However, in the case of TGF-β-induced EMT, HDAC9 suppression barely inhibited the phenotypic change of HuH1 cells, suggesting that HDAC9 does not locate in the upstream of EMT induction mediated by TGF-β-SMAD or non-SMAD pathway [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, HDAC9 is induced via signal transducer and activator of transcription 3 (STAT3) signaling to proliferate by PDAC-secreted proangiogenic factors [ 24 ]. HDAC9 is reported to be regulated post-transcriptionally by several micro RNAs in retinal, oral, breast, and gastric cancer, and as being associated with poor prognosis [ 21 , 23 , 25 , 26 ]. Analysis of other signaling pathways that induce dedifferentiation and malignant phenotype via HDAC9 may help us to understand the essential role of HDAC9 in tumor dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments for retinoblastoma include chemotherapy, plaque radiotherapy, external beam radiotherapy, cryotherapy and surgery ( 2 ). However, despite the clinical response to such comprehensive strategies, tumour metastasis and extraocular invasion in the advanced stage still cause death in children ( 3 , 4 ). Therefore, investigation of the underlying mechanism of retinoblastoma tumourigenesis and development is necessary to improve therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%